Competition between light-induced and intrinsic nonadiabatic phenomena in diatomics - Csehi, András; Cederbaum, Lorenz S. (The journal of physical chemistry letters, 2017)
Nonadiabatic effects arise due to avoided crossings or conical intersections that are either present naturally in field-free space or induced by a classical laser field in a molecule. Recently, it was demonstrated that nonadiabatic effects in diatomics can also be created in an optical cavity. Here, the quantized radiation field mixes the nuclear and electronic degrees of freedom. We show the equivalence of using the cavity’s quantized field and the classical laser field as usually done for molecules. This is demonstrated for NaI, which exhibits a pronounced natural (intrinsic) avoided crossing that competes with the avoided crossing induced by the field. Furthermore, rotating molecules exhibit light-induced conical intersections (LICIs) in classical laser light, and we also investigate the impact of these intersections. For NaI, we undoubtedly demonstrate a significant difference between the impact of the laser-induced avoided crossing and that of the LICI on the dynamics of the molecule.